Proyecto de factibilidad para la agro industrialización artesanal de café robusta que produce la organización Kichwa Kallari Kawsay - 24 de mayo - cantón Loreto de la provincia de Orellana. - Grefa Yumbo, Dinora Lizbeth (2014)
The Antisuyo Ally Kapya Cía. Ltd. Company means " Good Amazon Coffee " it will be dedicated to the agro industrial craft of robusta coffee, which is produced by the Kichwa Kallari Kawsay organization - May 24, which includes several families involved in the planting, tending and harvesting, they have organic certification that guarantees the quality of the raw product, in which we transform it into a 100% pure and organic drink, with the object of being a brand leader Café Ally Llikchachik - "Great awakening”. After a thorough market analysis, cost calculations of plants, machinery, supplies, equipment, personnel, capital and that of third parties, income and expenses, it was determined that it generates a profitable return from the sale of this product without leaving the origin of our cultural identity and also with the environmental impact assessment we defend and promote the productive resources of the Amazon.